Cosmopolitan localism as a research framework for sustainability in graphic design practices. Issue 2 (3rd April 2022) - Bonsu, Ginn Assibey; Chisin, Alettia V.; Cronje, Johannes
ABSTRACT: Graphic design practices in a developing nation have a negative impact on sustainability, with researchers recommending several strategies to minimize it, yet much has not been achieved. Cosmopolitan localism has been proposed as a solution since contextual problems need contextual solutions. This paper attempts to establish a relationship between cosmopolitan localism and sustainability through exploring emerging innovations in cosmopolitan localism and their potential to minimize the impact of graphic design practices on sustainability. Data were gathered through observation, field notes of shared experiences, and unstructured interviews pertaining to designing packagings, labels, advertisement materials and by-products of graphic design production. The emerging innovations reflect three approaches, namely design policy, up-cycling of graphic design production by-products, and social media usage for design product dissemination. Results show how local approaches that are open and connected shape design decisions and reflect a connection to the global flow of ideas that minimize the impact of graphic design practices on sustainability. The paper concludes that cosmopolitan localism is a collaborative mode of production that creates an enabling environment for the practice of sustainability in graphic design, and that promotes distributed economics.